2005
DOI: 10.1002/ejic.200400825
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Chemistry of the Carbenoid Butadienyl Complex Ion [CpCo(σ,η4‐C4HMe4)]+ Formed by Protonation of the Cyclobutadiene Complex [CpCo(C4Me4)]

Abstract: The protonation of [CpCo(C 4 Me 4 )] (1) with excess acid, which produces the carbenoid ion 3 + , is shown to be reversible under conditions of low proton activity. Treatment of 3 + with one equivalent of NEt 3 mainly produces 1 (60 %, isolated yield), and in DMSO the solvent acts as base transforming [3]BF 4 into 1 (67 %, isolated yield). Deprotonation of [3]BF 4 with excess NEt 3 affords (cyclopentadienyl)[(2-5-η)-(3Z,4Z)-3,4-dimethylhexa-1,2,4-triene]cobalt (5) in high yield (83 %). The structure of 5 has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Electron-poor metallocenes such as Cp 2 Ti­(CCR) 2 or [Cp 2 Co] + (Cc + ) , were successfully incorporated as electron acceptors in CT systems. Compared to the ubiquitous Fc/Fc + couple, the Cc/Cc + couple has been less often employed in CT and PET schemes. ,, This underdeveloped attention is certainly due to the more difficult and less established substitution chemistry of Cc + . Only in the last years have the groups of Bildstein and Heck put forward reliable routes toward important Cc + key building blocks, such as [Cc-Br] + , [Cc-NO 2 ] + , [Cc-N 3 ] + , [Cc-COOH] + , or [Cc-NH 2 ] + . , …”
Section: Introductionmentioning
confidence: 99%
“…Electron-poor metallocenes such as Cp 2 Ti­(CCR) 2 or [Cp 2 Co] + (Cc + ) , were successfully incorporated as electron acceptors in CT systems. Compared to the ubiquitous Fc/Fc + couple, the Cc/Cc + couple has been less often employed in CT and PET schemes. ,, This underdeveloped attention is certainly due to the more difficult and less established substitution chemistry of Cc + . Only in the last years have the groups of Bildstein and Heck put forward reliable routes toward important Cc + key building blocks, such as [Cc-Br] + , [Cc-NO 2 ] + , [Cc-N 3 ] + , [Cc-COOH] + , or [Cc-NH 2 ] + . , …”
Section: Introductionmentioning
confidence: 99%
“…28 Substi-tuted derivative 32 can be prepared from half-sandwich complex CpCo(C 9 H 16 ) through the addition of tert-butyl isocyanide. 29 Planar-chiral cobaltoceniums 33-35 were prepared using achiral trisubstituted Cp's as starting materials in the same way. 30 A more-complicated helical cobaltocenium was reported by Katz, Geiger, Rheingold, and co-workers (Figure 5).…”
Section: Figure 3 Synthesis Of Disubstituted Cobaltoceniums With Boryl Ligandsmentioning
confidence: 99%
“…93 The σ:η 4 -butadienyl complex 161 was deprotonated with NEt 3 , affording the hexatriene complex 164 as an isomer of the CpCo-capped cyclobutadiene 159 (Scheme 42). 94 Careful investigations of this protonation/deprotonation equilibrium have shown that the cyclobutadiene complex 159 is thermodynamically more stable than the hexatriene complex 164. Complex 161 also shows a fascinating ring formation (and in terms of starting from the cyclobutadiene in total a ring enlargement) when it is reacted with tert-butyl isocyanide.…”
Section: Ring Enlargement Reactionsmentioning
confidence: 99%
“…Complex 161 also shows a fascinating ring formation (and in terms of starting from the cyclobutadiene in total a ring enlargement) when it is reacted with tert-butyl isocyanide. 94 This very fast reaction is carried out at -35 °C, and the resulting cobaltocenium ion 165 was obtained in about 90% yield.…”
Section: Ring Enlargement Reactionsmentioning
confidence: 99%
See 1 more Smart Citation